Kadar Apo-B dan Ketebalan Dinding Aorta Abdominalis Tikus Hiperkolesterolemia dengan Perlakuan Buah Jambu Biji Merah: Apo-B Levels and Abdominal Aortic Wall Thickness in Hypercholesterolemic Rats Treated with Red Guava Fruit - Sugeng Maryanto; Dian Oktianti (Amerta Nutrition, 2023)
Background: Coronary heart disease (CHD) is mainly related to hypercholesterolemia. Sometimes CHD occurs in people with normal cholesterol. Therefore, it is necessary to study other factors that cause CHD: apolipoprotein B (apo-B). Atherosclerosis is a marker of CHD, characterized by the thickening of the walls of blood vessels and the narrowing of blood vessels. Non-pharmacologically, CHD can be managed by consuming foods with high fiber and antioxidants, such as red guava fruit.  Objectives: This research aimed to analyze the consequence of red guava fruit on the Apo-B levels and the thickness of the abdominal aortic wall in hypercholesterolemic rats.  Methods: The research design was a pre and post-test and a randomized control group. Fifty hypercholesterolemic adults male Sprague Dawley rats were given red guava fruit. The primary treatment used red guava fruit as a treatment group, referring to the fiber requirement of 38 g/day, and simvastatin as a positive control group based on a human dose of 10 mg/day, the conversion of human to mouse dose, according to Laurence-Bacarach is 0.018. The negative control group was hypercholesterolemic rats. The standard feed for the rats was based on AIN93. The Enzyme-linked Immunosorbent Assay method measures apo-B levels, Kit For apo-B Rattus norwegicus, Catalog No. E92003Ra, produced by Uscn Life Science Inc. The aorta was taken after going through general anesthesia and thoracotomy. Furthermore, the aorta was processed for making histological preparations with hematoxylin-eosin (HE) staining to observe histopathological changes.  Results: Observation of aortic wall thickness using a microscope with a magnification of 400X. Simvastatin and red guava fruit have reduced Apo-B by 7% and 6%, respectively.  Conclusions: The performance of red guava fruit in reducing Apo-B concentration and the thickness of the abdominal aortic wall was equal to the simvastatin.